Feasibility assessment of patient-controlled EEG home-monitoring: More results from the HOMEONE study. (August 2022) - Baum, Ulrike; Baum, Anne-Katrin; Deike, Renate; Feistner, Helmut; Markgraf, Bernd; Hinrichs, Hermann; Robra, Bernt-Peter; Neumann, Thomas
Highlights: The feasibility of patient-controlled EEG home-monitoring was demonstrated. Patients were able to use an EEG home-monitoring device without medical assistance after training. The patient-controlled EEG home-monitoring resulted in substantial changes of patient management for 11% of patients. Abstract: Objective: The feasibility phase of the HOME (Ho me-M onitoing and E ducation) project aims to show the practical feasibility of Electroencephalography (EEG) home-monitoring using a patient-controlled mobile system. Its objective is to assess the potential diagnostic and therapeutic yields of home-monitoring compared to conventional healthcare. Methods: 16 office-based practitioners chose 97 patients and recorded standard 20-minute EEGs using conventional recorders. After training, the same patients used a patient-controlled mobile dry electrode EEG system in their home environment. The practitioners in charge and two additional raters assessed all recordings. We conducted inter-rater and intra-rater comparisons between the diagnostic findings. Results: 89 patients successfully conducted home-monitoring recordings. The intra-rater comparison results for the diagnostic findings of the conventional recordings and the patient-made recordings show a fair Cohen's kappa value (0.21). Additionally, we documented a change of patient management in 9 cases. Conclusions: The feasibility of EEG home-monitoring using a patient-controlled device is confirmed. The yield of EEG home-monitoring comprises information that can influence patient management. Significance: Patient-controlled EEG home-monitoring is feasible as part of routine care for neurological outpatients as its technical efficacy and practical feasibility are shown and significantly positive effects on patient management are evidenced.